2005
DOI: 10.1055/s-2005-865316
|View full text |Cite
|
Sign up to set email alerts
|

The Photo-Dehydro-Diels-Alder Reaction: An Efficient Route to Naphthalenes

Abstract: The photo-dehydro-Diels-Alder reaction (PDDA), a new photochemical route to naphthalenes is presented. The [4+2] cycloaddition takes place between 3-arylynones and arylacetylenes, in which these moieties may be located in two molecules (intermolecular PDDA, 1) or in the same molecule (intramolecular PDDA, 5 and 9). Especially the latter approach is attractive from a preparative point of view and permits a straightforward access to highly functionalized naphthalenes. The irradiation of unsymmetrical reactants 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
0
15
2
1
Order By: Relevance
“…In contrast to our previous observation [5], we found that the Me group in the attacked position does not undergo a 1,2-migration, but is obviously trapped by the solvent (XH) from cycloallenes CA(1) and CA(3), respectively (Scheme 5). Although the naphthalenes 12m (from 1m) and 11n (from 1n) were formed as main products, we also isolated compounds 16 and 17, originating from an attack of the mesityl group.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our previous observation [5], we found that the Me group in the attacked position does not undergo a 1,2-migration, but is obviously trapped by the solvent (XH) from cycloallenes CA(1) and CA(3), respectively (Scheme 5). Although the naphthalenes 12m (from 1m) and 11n (from 1n) were formed as main products, we also isolated compounds 16 and 17, originating from an attack of the mesityl group.…”
contrasting
confidence: 99%
“…treatment with lithium phenylacetylide (LPA). MeO(Me)NH · HCl, (i-Pr) 2 described [5], we assume that the photochemical ring-closure proceeds via the biradicals BR(1) as intermediates (Scheme 4). Finally, the target ketones 1o -r were obtained in two steps via the corresponding Weinreb amides (WA).…”
mentioning
confidence: 99%
“…The Photo-Dehydro-Diels-Alder (PDDA) reaction has been proven as versatile method for the preparation of highly functionalized aryl-naphthalenes and binaphthyles [1][2][3][4][5][6]. In continuation of this work, we investigated the capability of the PDDA reaction for macrocyclizations.…”
Section: Discussionmentioning
confidence: 99%
“…This synthetic approach differs from most other routes to naphthalenophanes in that the naphthalene moiety is not present in the reactants but is formed in the cyclization step by means of the Photo-Dehydro-Diels-Alder (PDDA) reaction [6,7], which is a special case of the Dehydro-Diels-Alder (DDA) reaction [8]. In recent years we have intensively investigated the PDDA reaction and established it as a powerful method for the preparation of biaryls [9,10,11,12,13]. Herein we report in continuation of the above mentioned work on the synthesis of 1,6- and 1,8-naphthalenophanes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%